2012
DOI: 10.1111/j.1447-0756.2012.01897.x
|View full text |Cite
|
Sign up to set email alerts
|

Using phonocardiography to investigate maternal cardiac reserve function in gestational hypertension and pre‐eclampsia

Abstract: Our findings indicate that cardiac reserve function declines with the increasing severity of hypertension during pregnancy. Phonocardiography is a useful, convenient and clinically worthwhile technique to monitor cardiac reserve function parameters of pregnant women with pre-eclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…A previous study showed that the D/S is a noninvasive indicator for evaluating cardiac reserve. Application of the D/S to cardiac function assessment in various populations, such as preterm infants, 13 neonates, 14 healthy young people 15 and pregnant women, 16 has been studied. Nevertheless, measurement of the D/S among different CHF phenotypes has not been investigated, and its associations with echocardiography measurements has received little attention and has not previously been revealed.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that the D/S is a noninvasive indicator for evaluating cardiac reserve. Application of the D/S to cardiac function assessment in various populations, such as preterm infants, 13 neonates, 14 healthy young people 15 and pregnant women, 16 has been studied. Nevertheless, measurement of the D/S among different CHF phenotypes has not been investigated, and its associations with echocardiography measurements has received little attention and has not previously been revealed.…”
Section: Discussionmentioning
confidence: 99%
“…Our team also studied the application of D/S ratio indicator in other fields, such as in preterm infants [6], in neonates [7], in healthy children aged 1 -18 years [5,8,9], in children with atrial septal defect [10], in coal miners [11], in pregnant women [12][13][14], and in middle-aged and elderly person [15]. The corresponding data of D/S ratio were obtained, which have been used to evaluate cardiac functional status in healthy persons or patients.…”
Section: Applications Of D/s Ratio Indicatormentioning
confidence: 99%